Enhancing Students’ Science Process Skills Through PjBL in Acid-Base Titration Experiment - Ayu Tri Khodizah; Ni Pt. Pande Mirah Surya Dewi; Indah Langitasari; Irah Namirah (Universitas Lambung Mangkurat, 2025)
Science process skills (SPS) are essential competencies in 21st-century education. This study aimed to evaluate the effectiveness of the Project-Based acid-based titration project. A pre-experimental one-group pretest-posttest design was applied to 32 high school students in Serang City. Instruments included observation sheets and 28 essay items, validated by 10 experts using CVR (38 items retained, CVR ≥ 0.62) and tested for reliability (Cronbach's alpha = 0.542). Data were analyzed using the Shapiro-Wilk test, paired sample t-test, N-Gain, and effect size. Results showed a significant improvement in SPS, with pre- and post-test mean scores increasing from 40.00 to 74.34. The t-test yielded t(31) = -21.417, p < 0.001, and effect size was high (μ = 0.97). N-Gain analysis indicated moderate improvement in most indicators—such as planning steps (0.63), identifying patterns (0.65), and applying concepts (0.63)—but low gains in hypothesizing alternatives (0.04) and interpreting graphs (0.15). These findings suggest that PjBL is an effective strategy for developing SPS in practical chemistry contexts, preparing students for scientific reasoning and inquiry in the industrial era 4.0.